Денискины рассказы - Драгунский Виктор Юзефович (Серия "Школьная библиотека", 2012)
Экземпляры: ф. 4 (20140417) / Инвентарный номер: 101060 / Цена: 96.80 / Авт.знак: Д 72 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6